The Korean Pop Variety Show Effect: English as a Foreign Language Learners’ Perception of Using Going Seventeen English Subtitles for Vocabulary Learning - Kusumah, Nayla Faradilla; Ratri, Devinta Puspita (Universitas Pahlawan Tuanku Tambusai, 2026)
K-Pop variety shows have gained global popularity through the use of English subtitles, enabling them to reach a broader international audience. Some English as a Foreign Language (EFL) learners utilize these shows to enhance their English skills by watching popular K-Pop variety programs such as Going Seventeen. This study investigates EFL students’ perceptions of using English subtitles in Going Seventeen for vocabulary acquisition. The participants were Indonesian students who are fans of Seventeen (Carats) and regularly watch Going Seventeen with English subtitles. Data were collected through an online questionnaire focusing on perceived benefits, real-life effects, and challenges. The findings indicate that most participants perceived the use of English subtitles positively, with all questionnaire items receiving responses above 40%. The results suggest that English subtitles in Going Seventeen facilitate vocabulary learning by making content easier to understand, enjoyable, and motivating. Nevertheless, some participants reported difficulties in maintaining focus on subtitles while learning vocabulary. Overall, the study highlights the potential of K-Pop variety shows as an effective and engaging resource for vocabulary learning.